Tadabbur Ayat Kauniah Tentang Fotosintesis di Panti Asuhan Al-Ihsan Banjarmasin - Gusti Hadiatus Solehah; Muhammad Arbain; Khairullah Khairullah (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2026)
This community service program aimed to enhance the scientific understanding and spiritual awareness of children at Al-Ihsan Orphanage, Banjarmasin, by integrating the concept of photosynthesis with contemplation (tadabbur) of the Koranic cosmic verses (Ayat Kauniyah). The program was designed to foster participants' appreciation of the harmony between scientific knowledge and Islamic teachings while promoting environmental awareness. The methods employed included interactive lectures, Koranic verse exploration, group discussions, demonstrations of the photosynthesis process, hands-on tree planting activities, and pretest and post-test evaluations. The program involved 15 orphanage children who actively participated in all learning activities. The results demonstrated a significant improvement in participants' understanding of the relationship between photosynthesis and the Koranic verses, as indicated by an increase in the average score from 54.67 on the pretest to 65.33 on the post-test. In addition, participants showed greater enthusiasm for learning science through an Islamic perspective and developed stronger environmental responsibility by recognizing plants as signs of Allah's greatness and essential components of life. Overall, the program successfully integrated scientific concepts with Koranic values, creating meaningful learning experiences that strengthened scientific literacy, religious understanding, and environmental stewardship among the participants.